2010
DOI: 10.1038/emboj.2010.215
|View full text |Cite|
|
Sign up to set email alerts
|

Plant virus-mediated induction of miR168 is associated with repression of ARGONAUTE1 accumulation

Abstract: Virus infections induce the expression of ARGONAUTE1 (AGO1) mRNA and in parallel enhance the accumulation of miR168 (regulator of AGO1 mRNA). Here, we show that in virus-infected plants the enhanced expression of AGO1 mRNA is not accompanied by increased AGO1 protein accumulation. We also show that the induction of AGO1 mRNA level is a part of the host defence reaction, whereas the induction of miR168, which overlaps spatially with virus-occupied sectors, is mediated mainly by the Tombusvirus p19 RNA-silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
187
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(221 citation statements)
references
References 59 publications
19
187
0
3
Order By: Relevance
“…1A and B). Altogether, our data showed that, in contrast with the situation observed for representative RNA viruses (42,60), the effect of viroid infection on AGO1, if any, is not mediated by miR168 targeting of AGO1 mRNA.…”
Section: Resultsmentioning
confidence: 42%
See 2 more Smart Citations
“…1A and B). Altogether, our data showed that, in contrast with the situation observed for representative RNA viruses (42,60), the effect of viroid infection on AGO1, if any, is not mediated by miR168 targeting of AGO1 mRNA.…”
Section: Resultsmentioning
confidence: 42%
“…As indicated above, AGO1 is a key player in the antiviral defense mediated by RNA silencing. Infection by plant RNA viruses induces and reduces the accumulation of AGO1 mRNA and AGO1 protein, respectively (42,60). The explanation for this apparent paradox is that expression of AGO1 mRNA is translationally repressed by miR168 (61), the accumulation of which is elicited by virus infection (42,60).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR168 plays a pivotal role as it regulates the expression of AGO1, a mechanism through which all microRNAs can down-regulate their targets Gazzani et al, 2009). In addition, miR168 is reportedly involved in the regulation of plant growth, fruit development, and response to different stresses, such as UV-B and aluminum, and is also up-regulated during viral infection in plants, during which it is ubiquitous in plant-virus interactions (Várallyay et al, 2010;Lima et al, 2011;Wang et al, 2013;Xian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited information is available on the interaction of each miRNA with its target genes. For example, the translation of AGO1 mRNA is inhibited by miR168, which is induced by p19 RNA-silencing suppressor (Várallyay et al, 2010), while miR403 induces the post-transcriptional silencing (cleavage) of the AGO2 gene via interaction with AGO1 (Allen et al, 2005;Harvey et al, 2011). MEMB12 mRNA is targeted by miR393b* in association with AGO2, which is induced by DC3000 (Zhang et al, 2011b).…”
Section: Prediction and Expression Of Putative Target Genes Of Gamma-mentioning
confidence: 99%